Cross-field collaboration and the uptake of non-peer-reviewed working papers into public policies: Evidence from the NBER - Zhixiao Li; Qianjin Zong; Lixue Lin; Hongjin Xu; Xiaoqian Shi (Journal of Information Science, 2026)
Evidence-informed policymaking increasingly utilizes non-peer-reviewed research, such as working papers. While the link between cross-field collaboration and the academic uptake of peer-reviewed research is established, its relationship to the translation of non-peer-reviewed research into public policy remains unexplored. This study aims to address the gap by examining the association between cross-field collaboration and policy uptake of such pre-publication research. Working papers ( n = 19,280) released between 2000 and 2019 by the National Bureau of Economic Research, an economics research think tank, were selected as a sample. Negative binomial regression models were employed to assess the relationship between cross-field collaboration and policy uptake. The results revealed that cross-field collaboration significantly and positively correlated with the uptake of working papers by public policies. The finding establishes a positive association between the collaborative nature of research production and its subsequent policy influence, even for pre-publication outputs. This research provides novel insights into the mechanisms through which pre-publication research influences policy development. By establishing the relationship between cross-field collaboration and policy uptake, the study contributes to understanding how academic research translates into practical policy applications. The findings have important implications for researchers and research institutions seeking to maximize the social impact of their research, as well as for policymakers assessing the quality and relevance of non-peer-reviewed evidence.